2021
DOI: 10.3389/fmed.2021.675049
|View full text |Cite
|
Sign up to set email alerts
|

The FRAILMar Study Protocol: Frailty in Patients With Advanced Chronic Kidney Disease Awaiting Kidney Transplantation. A Randomized Clinical Trial of Multimodal Prehabilitation

Abstract: Introduction: Frailty is very frequent among patients with chronic kidney disease (CKD) who are awaiting deceased donor kidney transplantation (KT), and transplant outcomes are worsened in those frail recipients. Frailty and poor fitness powerfully predict mortality, kidney graft survival, and healthcare utilization after KT. Intervention is essential to improve survival and quality of life for frail CKD patients, regardless of their age. Studies of post-transplant physical therapy intervention have been met w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…Giving the large number of frailty scales, it is important to validate them in the renal population, clarifying their predictive value for bad outcomes [ 20 ] or analyzing the clinical significance of their definition for frailty. In addition, identifying pre-frail or frail patients may allow clinicians to establish proper strategies to revert the situation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Giving the large number of frailty scales, it is important to validate them in the renal population, clarifying their predictive value for bad outcomes [ 20 ] or analyzing the clinical significance of their definition for frailty. In addition, identifying pre-frail or frail patients may allow clinicians to establish proper strategies to revert the situation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing prehabilitation studies have predominantly focused on those awaiting transplant or approaching dialysis, concluding that prehabilitation has a positive influence on physical activity, frailty status, function, and strength [95][96][97]. Further definitive trials are required; an ongoing study by Perez-Saez et al will provide additional information on the role of prehabilitation, specifically in frail kidney transplant candidates [98]. Interestingly, no research has been conducted for those opting for conservative care.…”
Section: Acute and Inpatient Rehabilitationmentioning
confidence: 99%
“…Evidence from systematic reviews have suggested that although nutritional interventions delivered in isolation may not show a beneficial effect [110], when used as part of multi-component interventions incorporating physical exercise, they may provide an additive effect, yielding greater improvement in frailty status and physical functioning [111]. For people with frailty and CKD, several such trials are currently underway and will begin to shed light on the impact of multi-component interventions on frailty in people with CKD stage 3-5 [51], those receiving haemodialysis [112], and in kidney transplant recipients [98].…”
Section: Nutritionmentioning
confidence: 99%
See 2 more Smart Citations